Water Filtration Design for Rainwater Harvesting System in Faculty of Civil Engineering and Built Environment, UTHM - Zainun, Noor Yasmin; Ashri, S.; Mohammad, H.; Mohammed Ghazali; F. E.; Khahro, S. H. (Recent Trends in Civil Engineering and Built Environment, 2020)
Rainwater harvesting system is an integrated environment friendly system that relief in reducing the surface runoff which involve in the process of sustainable urban water resources development. One of the rainwater harvesting system component is water filtration system which able to ensure a good quality harvested rainwater will be produced. Collected rainwater were expose to the atmosphere that may contain contaminants which may affect human health as it contribute direct contact with human skin. This study aim for proposing a suitable media filter for the installed water filtration system at Faculty of Civil Engineering and Built Environment (FKAAB) building. Besides, harvested rainwater quality were measured to identify the class of water based on the National Water Quality Standard for Malaysia through sampling and testing process. This study conducted through some process which were investigation of Rainwater Harvesting System (RWHS) in FKAAB building, sampling and Water Quality Index (WQI) testing process of harvested rainwater, classification of harvested rainwater and selection of media filter for filtration system. Result form the investigation show that RWHS in FKAAB building utilized a mineral tank for waterfiltration system which required various layers of media filter. Harvested rainwater were classified as Water Class 3. Therefore, five layers of filter media were proposed consisting of natural material such as gravel, sand, charcoal, clam shell and peat soil that able to filtrate any large and small debris, remove odour and taste, filtrate heavy metal and decompose any organic compound content in water.